Obesity in pregnancy: infant health service utilisation and costs on the NHS. Issue 11 (26th November 2015) - Morgan, Kelly L; Rahman, Muhammad A; Hill, Rebecca A; Khanom, Ashrafunnesa; Lyons, Ronan A; Brophy, Sinead T
Abstract : Objective: To estimate the direct healthcare cost of infants born to overweight or obese mothers to the National Health Service in the UK. Design: Retrospective prevalence-based study. Setting: Combined linked anonymised electronic data sets on a cohort of mother–child pairs enrolled on the Growing Up in Wales: Environments for Healthy Living (EHL) study. Infants were categorised according to maternal early-pregnancy body mass index (BMI): healthy weight mother (18.5≤BMI<25 kg/m 2 ; n=342), overweight mother (25≤BMI≤29.9 kg/m 2 ; n=157) and obese mother (BMI≥30; n=110). Participants: 609 singleton pregnancies with available health service records and an antenatal maternal BMI. Primary outcome measure: Total health service utilisation and direct healthcare costs for providing these services in the year 2012–2013. Costs are calculated as cost of the infant (no maternal costs considered) and are related to health service usage from birth to age 1 year. Results: A strong association existed between healthcare usage cost and BMI (p<0.001). Mean total costs were 72% higher among children born to obese mothers (rate ratio (RR) 1.72, 95% CI 1.71 to 1.73) compared with infants born to healthy weight mothers. Higher costings were attributed to a significantly greater number (RR 1.39, 95% CI 1.04 to 1.84) and duration (RR 1.55, 95% CI 1.37 to 1.74) of inpatient visits and a higher number of general practitioner visits (RR 1.10, 95% CI 1.03 to 1.16). Total mean additional resource cost was estimated at £65.13 for infants born to overweight mothers and £1138.11 for infants born to obese mothers, when compared with infants of healthy weight mothers. Conclusions: Increasingly infants born to mothers with high BMIs consume additional health service resources in the first year of life; this was apparent across inpatient and general practitioner services. Considering both maternal and infant health service use, interventions that cost less than £2310 per person in reducing obesity early pregnancy could be cost-effective.